2016
DOI: 10.4238/gmr.15037265
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of quercetin on acute lung injury in rats with sepsis and its influence on ICAM-1 and MIP-2 expression

Abstract: ABSTRACT. This study aimed to explore the protective effect of quercetin on acute lung injury (ALI) in rats with sepsis and the related mechanism. Rats were administered different doses of quercetin intraperitoneally, and blood samples and lung tissue were collected at 24 h after treatment. Arterial blood gases, lung water content, protein content, and cell counts in bronchoalveolar lavage fluid (BALF) were measured. Morphological changes in lung tissue pathology were observed under a light microscope. Serum i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Cytokines released by macrophages can stimulate endothelial cells to express ICAM-1 for leukocyte adhesion onto the vascular endothelium ( Peres et al, 2016 ). Meng et al (2016) reported that quercetin decreased the number of leukocytes recruited to lung tissues and inhibited ICAM-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines released by macrophages can stimulate endothelial cells to express ICAM-1 for leukocyte adhesion onto the vascular endothelium ( Peres et al, 2016 ). Meng et al (2016) reported that quercetin decreased the number of leukocytes recruited to lung tissues and inhibited ICAM-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Meng et al (2016) studied the protective effect of quercetin on acute lung injury in rats with sepsis by administration of the compound at doses of 30 and 50 mg/kg. Quercetin showed improvement in arterial blood gases, lung water content, protein content, and cell counts in bronchoalveolar lavage fluid in comparison to control model group.…”
Section: Quercetinmentioning
confidence: 99%